The effects of structured telephone call, WhatsApp text messaging and chewing gum on orthodontic anxiety - Cheong, Joo Ming (2022)
Background: Anxiety is a significant side effect during orthodontic treatment. Non-pharmacological methods may have an effect in decreasing anxiety level among patients undergoing orthodontic treatment. Purpose: To investigate whether there was a difference in self-reported state anxiety among patients with orthodontic separator placement between postprocedural telephone call, text messaging, chewing gum and control group. Methodology: Eighty female orthodontic patients were randomly assigned to one of four groups (structured telephone call, WhatsApp text messages follow-up, sugar-free chewing gum and control). Subjects in the first three groups received the interventions after 24 hours of orthodontic separator placement, and completed the state component in state-trait anxiety inventory (STAI) questionnaire to assess their level of anxiety before separator placement, immediately after, at 24 hours and daily for seven days. One-way repeated measure ANOVA was conducted to compare the effects of non-pharmacological methods on the mean state anxiety level at different time points. Results: There was significant difference in mean state anxiety level among the four groups at p<.001. Post hoc comparisons revealed significant difference between chewing gum and control groups at day-2 until day-7 (p<.001), and significant difference between WhatsApp text messaging and control groups at day-3 until day-7 (p<.05), as well as between telephone call and control groups at day-4 until day-7 (p<.05). However, there were no differences in mean anxiety level between telephone call, WhatsApp text messaging and chewing gum groups in all time points. At day-7, chewing gum group had the lowest mean state anxiety level (28.00  10.81), followed by telephone group (30.95  9.58), WhatsApp text message group (33.15  11.41) and lastly control group (41.90  13.23). Conclusion: Structured telephone call, WhatsApp text messaging and chewing gum conferred better anxiety reducing effect in patients with separator placement during orthodontic treatment compared to no treatment.